The effects of quantum energy surgical device and of bipolar coagulation: A comparative experimental study - (:unkn) unknown (SPRINGER WIEN, 2002)
Objective. The quantum energy surgical device (QESD) employs an innovative, no-touch thermal coagulation, incision and evaporation technique in which thermal energy is delivered to tissue in the format of high-energy neutral argon gas atoms. The aim of this study is to compare QESD and bipolar coagulation (BC) through assessment of both haemostasis and histological damage to isolated femoral arteries of rats. Methods. Sxity rats were randomly divided into acute and short-term experimental groups. In the acute group (n = 20) histopathological evaluation was performed immediately following coagulation, whereas in the short-term experimental group (n = 20) the evaluation was performed 10 days later. Each sham group consisted of ten rats. Viewed under the surgical microscope, only normal-appearing, freshly sectioned, and bleeding femoral arteries were studied. Right femoral arteries subject to QESD coagulation, and left femoral arteries to BC. Haemorrhaging was controlled using the minimal coagulation time necessary to stop it. All vascular layers, including endothelium, internal elastic lamina, media and adventitia were examined histologically and ultrastructurally in a blind fashion to critically compare morphological damage due to QESD and BC. Results. Surgical haemostasis induced by QESD was found to be as safe as BC. Light microscopy revealed more marked histopathological changes in the BC than in the QESD group. These involved mainly the endothelial and medial compartments and, at the ultrastructural level, consisted of endothelial degeneration and exfoliation, irregularity of internal elastic lamina, degeneration, and loss of medial smooth muscle. Conclusion, The results indicate that QESD coagulation induces significantly less histological damage than does BC. Thus QESD coagulation is a safe, less tissue destructive, and equally effective method of haemostasis.
Keywords: Argon plasma scalpel; bipolar coagulation; haemostasis; quantum energy surgical device; ARGON-PLASMA COAGULATION; BEAM COAGULATOR; SURGERY; ESOPHAGUS; EXPERIENCES; HEMOSTASIS; APC